Evaluation of the Accuracy of Point-of-Care Urine Chloride Measured via Strip Test in Patients with Heart Failure - Mateusz Guzik; Berenika Jankowiak; Piotr Ponikowski; Jan Biegus (Biomedicines)
Background: In clinical practice, patient self-monitoring is crucial in achieving therapeutic goals in various diseases. In heart failure (HF), it is particularly important due to the increasing role of urine composition. Therefore, we proposed this study to assess the accuracy of urine chloride (uCl−) assessment via strip test in relation to chloride and sodium (uNa+) measurements in a gold-standard laboratory method. Methods: Urine samples were collected before administering morning medications. Afterwards, they were analyzed concurrently using the strip test and gold-standard laboratory method. Results: The study cohort comprised 66 patients (82% male, mean age 68 ± 12 years), of whom 65% were diagnosed with HF and 35% without HF. Across the entire cohort, a strong correlation was observed between uCl− measured by both methods (r = 0.85; p < 0.001). However, the strip test was found to underestimate uCl− relative to the laboratory measurements (mean difference of 18 mmol/L). Furthermore, strong correlations were observed between the methods among patients with HF and without HF (r = 0.88 vs. r = 0.71, respectively; p < 0.001 for both), where they presented similar relationship patterns. Interestingly, in patients with a low glomerular filtration rate (eGFR ≤ 60 mL/min/1.73 m2), the correlation between both methods was greater compared to those with high eGFR (>60 mL/min/1.73 m2) (r = 0.94 vs. r = 0.76, respectively; p < 0.001 for both). The relationship between uCl− from the strip test and uNa+ from the laboratory measurement was weaker than for uCl−, but it was significant. Conclusions: These findings suggest that point-of-care strip tests for assessing urinary chloride demonstrate high accuracy and potential utility, particularly in patients with reduced eGFR.